Empowering vocational teachers through digital innovation: Enhancing QR code-based learning media - Hidayat, Nuzul; Sardi, Juli; Putra, Rido; Ranuharja, Fadhli; Ismi, Riwayatul; Jamhur, Annisak Izzaty (Community Empowerment, 2025)
The development of digital technology requires vocational education (SMK) teachers to be able to develop innovative learning media, such as QR codes, to support 21st-century learning. This community service activity aimed to improve the skills of teachers at SMKN 1 Padang Panjang in designing and implementing QR code-based digital learning media integrated with the Activities Digital Learning (ADL) concept. This activity involved 20 teachers through stages of socialization, training, workshops, hands-on practice, and mentoring. The materials covered AI-assisted digital module creation, media design (Canva), video production (CapCut), and QR Code integration into ADL. The results of the pre-test and post-test evaluation showed an average increase of 35% in teachers’ digital skills. Furthermore, each teacher successfully created at least one ready-to-use QR code-based learning media product. This program also successfully established a collaborative network among teachers to support the sustainability of digital innovation at the school.